Synthesis of Dextran–Phenoxodiol and Evaluation of Its Physical Stability and Biological Activity - Yee, Eugene M. H.; Cirillo, Giuseppe; Brandl, Miriam B.; Black, David StC; Vittorio, Orazio; Kumar, Naresh (Frontiers in Bioengineering and Biotechnology, 2019)
Phenoxodiol, an isoflavene anti-tumor agent, was conjugated on the polysaccharide dextran using immobilized laccase as biocatalyst. The success of the enzymatic conjugation was determined by UV-vis spectrophotometry and its functionalization degree was assessed by 1H NMR and was found to be 3.25 mg phenoxodiol/g of conjugate. An accelerated stability test showed that the resultant conjugate was 9 times more stable than the free phenoxodiol when tested for its residual anti-oxidant activity with the Folin-Ciocalteu assay. In vitro anti-proliferative activity of the conjugate was evaluated against neuroblastoma SKN-BE(2)C, triple negative breast cancer MDA-MB-231, and glioblastoma U87 cancer cells. The conjugate was shown to be generally more potent than phenoxodiol against all three cell types tested. Additionally, cytotoxicity and anti-angiogenic activity of the conjugate was also evaluated against non-malignant human lung fibroblast MRC-5 and human microvascular endothelial cells HMEC-1, respectively. The conjugate was found to be 1.5-times less toxic than phenoxodiol while mostly retaining 62% of its anti-angiogenic activity in the conjugate form. This study provides further evidence that the conjugation of natural product-derived drugs onto polysaccharide molecules such as dextran can lead to better stability and enhanced biological activity of the conjugate compared to the free drug alone.